A single pixel tracking system for microfluidic device monitoring without image processing. (April 2022) - Ni, Mingyang; Deng, Huaxia; He, Xiaokang; Li, Yan; Gong, Xinglong
Highlights: An image-free method for monitoring microfluidics device is proposed. The data throughput of the proposed method is extremely low. Real-time processing is available for the method. The method achieves both high frame rate and long duration monitoring. Abstract: Currently image-based optical measurement methods are the main approaches for detecting and tracking the movements of droplets or particles in microfluidic devices. However, the massive image data throughput and high computational consumption of image processing have become challenges to achieve real-time and long-term monitoring. Here a single-pixel tracking system is proposed to monitor the microfluidic device on the basis of single-pixel imaging and microscope technology without image reconstruction. The experimental results of tracking droplet in microfluidic device demonstrate that the proposed system have unique potential advantages in dynamic tracking for microfluidic devices. The data throughput of the proposed method is 1/792 of image-based methods and can reach an equivalent frame rate of 312.5 Hz with a low computational consumption of 89.3 μs per frame. The proposed image-free tracking method provides a welcomed boost to the further development of microfluidic device monitoring and indicates a potential way to real-time and long-term monitoring without image processing.